Arenaeocoris enervatus (Hemiptera: Heteroptera: Reduviidae: Stenopodainae), a new genus and species from the Southeastern United States - Blinn, Robert L. (Zootaxa, 2012)
Arenaeocoris gen. nov., and a new species, A. enervatus sp. nov., is described from southeastern United States. Diagnosticcharacters to distinguish the new genus from related taxa in the United States, illustrations of the species, and a key to the genera for the United States incorporating the new genus, are provided.